Anaerobic granular sludge coupled with artificial aeration or Fe-based substrate enhanced nitrogen conversion dynamic based on CW-MFCs. (February 2022) - Wang, Jun-Feng; Zhu, Cong-Yun; Li, Qu-Sheng; Yan, Deng-Ming; Wang, Li-Li; He, Tao; Cai, Ze-Xiang; Zhou, Huan-Zhan; Song, Xin-Shan
Abstract: Nitrogen conversion, e.g. ammonification, nitrification, and denitrification, efficiency in constructed wetlands (CWs) was constrained by the lack of microbial biomass, electron acceptor, and supplemental electron transfer pathway due to its configuration defects. High density sludge inoculation, electron acceptor enrichment, and electron transfer intensification can respectively enhance the conversion efficiencies of different nitrogen forms in CWs. Thus, three approaches including anaerobic granular sludge (AGS) coupled with artificial aeration (R1) or Fe rich substrates (R2: Fe-C; R3: FeS) based on CW-microbial fuel cells (CW-MFCs) were explored to enhance nitrogen conversion dynamic. Results showed that the ammonification, nitrification, and denitrification efficiencies (Org-N loading rates: 2.1–4.4 g N/(m 2 ·d)) of three reactors could reach 89%, 34–80%, and 90%, respectively. Interactions of acetoclastic methanogens ( Methanosaeta ) and acid-producing bacteria ( Trichococcus ) play an important role in the conversion of Org-N to NH3 -N. Typical electricity-generating bacteria, such as Trichococcus, Clostridium, Rhodobacter, and Geobacter, enriched in anodic zone, especially for R2–3, which availed for Feammox process during the conversion of NH3 -N to NO2 -N and NO3 -N. Stable bioenergy output could act as a supplementary for electrochemical denitrification, inducing an approximately complete denitrification in CWs. In addition, CW-MFC associated with AGS exhibit a favorable organic degradation efficiency (68–90%) under the organic loading rates of 36–78 g COD/(m 2 ·d). These findings indicated that AGS coupled with artificial aeration or Fe-based substrates are promising technologies for promoting nitrogen conversion dynamic and achieving sustainably nitrogenous wastewater treatment based on CW-MFCs. Graphical abstract: Unlabelled Image Highlights: AGS with artificial aeration or Fe-based substrates enhance N dynamic in CW-MFCs. Methanosaeta and Trichococcus are key taxa in AGS for high-efficiency of ammoxidation. Fe-based substrates enriched exoelectrogens in anode of CW-MFCs, inducing Feammox. Exoelectrogens ensure bioenergy output and electrochemical denitrification in operation.